2010
DOI: 10.1111/j.1601-0825.2009.01609.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of oral lesion prevalence in renal transplant patients under immunosuppressive therapy and healthy controls

Abstract: OBJECTIVE: The aim of this study was to analyse the prevalence of oral lesions in a group of renal transplant patients (RTPs) compared with healthy controls (HCs). SUBJECTS AND METHODS: The study included 500 RTPs (307 men, 193 women, mean age 53.63 years) and 501 HCs (314 men, 187 women, mean age 52.25 years). Demographic and pharmacologic data were recorded for all subjects. RESULTS: Forty percent of the RTPs presented with oral lesions compared to 23.4% of HCs. The most frequent lesion was candidiasis (7.4%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
2
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 38 publications
(67 reference statements)
1
26
2
6
Order By: Relevance
“…The results of our study showed that renal transplant patients had significantly more oral lesions (31%) than the controls (12%), which is in line with studies by other authors (3,5,15). However, unlike the study by de la Rosa et al (9) in which the prevalence of oral lesions was 60%, in our patients, as in the study by López-Pintor RM et al (15), it was almost two times smaller.…”
Section: Gašpar I Surcontrasting
confidence: 52%
See 4 more Smart Citations
“…The results of our study showed that renal transplant patients had significantly more oral lesions (31%) than the controls (12%), which is in line with studies by other authors (3,5,15). However, unlike the study by de la Rosa et al (9) in which the prevalence of oral lesions was 60%, in our patients, as in the study by López-Pintor RM et al (15), it was almost two times smaller.…”
Section: Gašpar I Surcontrasting
confidence: 52%
“…Od bolesnika su zatraženi i podatci o suhoći usta na temelju pet sljedećih pitanja: (15). Za procjenu kvalitete sline proveden je i vitroadhezijski test stomatološ-kim zrcalom (16).…”
Section: Ispitanici I Metodeunclassified
See 3 more Smart Citations